Pressure induced crossover from 2D-like to 3D structural arrangement in van der Waals magnet CrBr3 - D.P. Kozlenko; O.N. Lis; N.T. Dang; S.E. Kichanov; E.V. Lukin; I.Yu. Zel; N.O. Golosova; B.N. Savenko; T.L. Phan; T.K. Dinh; T.A. Tran (ChemPhysMater, 2025)
The evolution of the structural and electronic properties of the van der Waals layered ferromagnet CrBr3 across the semiconductor-metal transition was investigated using X-ray powder diffraction and Raman spectroscopy at high pressures up to 38 GPa and by density functional theory (DFT) calculations at high pressures up to 120 GPa. The pressure behavior of the structural parameters and vibrational modes revealed a crossover from the quasi-two-dimensional system with weakly interacting atomic layers to the three-dimensional-like system with strongly interacting layers at P ≈ 15 GPa. This resulted in a significant modification of the pressure coefficients of the lattice parameters and interlayer distances. DFT calculations using first-principles generalized gradient approximations of the Perdew-Burke-Ernzerhof (PBE) and Perdew–Burke–Ernzerhof-sol (PBEsol) functionals qualitatively reproduced the high pressure effects on the structural and electronic properties of CrBr3, with more accurately results obtained by PBEsol. The relative increase of the binding energy absolute value between the van der Waals layers by 75 times in the pressure range up to 60 GPa was evaluated. Band gap closure associated with the semiconductor–metal transition was found at P = 60 GPa, which is higher than the experimentally determined value.